A Prospective study of Dry Eye after manual Small Incision Cataract Surgery in rural population of Bagalkot - Jayshree MP; Shivkumar Hiremath; Monalisha Pattnaik; Mallikarjun Salgar (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2017)
Aim: To find the occurrence of 'Dry Eye' and to assess the severity of the dry eye after manual small incision cataract surgery with corneoscleral tunnel incision. Material and Method: A total of 81 patients were selected who came for manual small incision cataract surgery. Each patient was questioned pre-operatively about 'dry eye' symptoms and examined with Schirmer's test 1 and tear fi lm break up time. Following this, the patients underwent small incision cataract surgery with a superior incision of 6-7mm depending on the grade of cataract. Schirmer's test 1 and tear film break up time test were repeated on post-operative day 1st, 7th & 30th day. Dryness of the eye was analysed and graded as per DEWS classifi cation 2007. Result: In the total sample, 96.6% patient had dry eye. Among them 13.79% had mild grade and 20.8%had moderate and 62.06% had severe grade. 37.93% were male and 65.5% were female.The mean age of patient was 58.18 with SD of 8.62.The difference in tear fi lm break up time before and 7days after cataract surgery was found to be clinically significant with p value 0.0001, which stabilises and become clinically insignificant after 30 days (p value 0.215). The difference in Schirmer's test before and 7days after cataract surgery was also found to be clinically significant with p value <0.01 and which becomes clinically insignifi cant after 30days with p value 0.111. Conclusion: Tear fi lm instability is a complication seen in early post-operative period of manual small incision cataract surgeries with corneoscleral tunnel. Such post-operative patients develop moderate to severe dryness of eye which improves after 1 month.